2021
DOI: 10.1186/s12885-021-08629-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic immune-related gene signature associated with tumor microenvironment of colorectal cancer

Abstract: Background The tumor microenvironment (TME) has significantly correlation with tumor occurrence and prognosis. Our study aimed to identify the prognostic immune-related genes (IRGs)in the tumor microenvironment of colorectal cancer (CRC). Methods Transcriptome and clinical data of CRC cases were downloaded from TCGA and GEO databases. Stromal score, immune score, and tumor purity were calculated by the ESTIMATE algorithm. Based on the scores, we di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In recent years, multiple gene signature-based risk assessment models have been increasingly used for predicting the prognosis of CRC patients ( Yang et al, 2020 ; Yuan et al, 2021 ; Yue et al, 2021 ), which can provide more accurate prediction of prognosis and survival than single gene biomarker. Furthermore, the utilization of mRNA signatures based on tumor and microenvironment features has a better predictive effect on CRC ( Zhu et al, 2020 ; Wang et al, 2021 ). However, few study has been concerned on the prognosis potential of ferroptosis-associated gene signatures in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple gene signature-based risk assessment models have been increasingly used for predicting the prognosis of CRC patients ( Yang et al, 2020 ; Yuan et al, 2021 ; Yue et al, 2021 ), which can provide more accurate prediction of prognosis and survival than single gene biomarker. Furthermore, the utilization of mRNA signatures based on tumor and microenvironment features has a better predictive effect on CRC ( Zhu et al, 2020 ; Wang et al, 2021 ). However, few study has been concerned on the prognosis potential of ferroptosis-associated gene signatures in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The scores of stromal cell and immune cell between stage I and stage III, stage IV were remarkably different, suggesting that the change of tumor microenvironment promoted the progression of tumor from early onset to middle and late stage. Immune infiltration and stromal cell analyses showed that the prognostic value of the risk model was related to the CRC immune system ( Liu et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the R package ConsensusClusterPlus (ConsensusClusterPlus, RRID : SCR_016954) for consistent clustering analysis and DESeq2 (DESeq, RRID : SCR_000154)for identification of differentially expressed genes (DEGs). To determine the optimal number of clusters, we evaluated the results using cumulative distribution function and incremental area analysis with different clusters (2)(3)(4)(5)(6)(7)(8)(9)(10). The DEGs with fold change > 1.5 and FDR < 0.05 were defined as subtype-specific.…”
Section: Consistent Clustering Analysis and Identification Of Differe...mentioning
confidence: 99%
“…Utilize glycolysis as the main source of energy metabolism to obtain a higher sugar-breaking capacity, allowing the conversion of glucose to lactate to generate adenosine triphosphate (ATP) (8). Recently, an increasing number of studies have indicated that the TME, including lactate as well as immune microenvironments, affects the progression of CRC as well as its clinical outcomes (9,10). Incidentally, tumor cells exhibit an aberrant increase in glycolysis, which generates a high concentration of lactic acid that is necessary for malignant proliferation.…”
Section: Introductionmentioning
confidence: 99%